Enterprise hegemony and embedded hierarchy network: The political economy and process of global compact governance in China - Hongsheng Ren (University of Oxford, Global Economic Governance Programme (GEG), 2013)
To understand and explain if the Global Compact initiatives really attract enterprises and how they could achieve the aims of making the enterprises self-regulatory, we must examine the motivations of the participants and determine if they changed their behaviors after joining the initiative. This paper investigates the determinants of Chinese enterprises' attitudes toward the United Nations Global Compact (UNGC) using interviews and data analysis of the Chinese participants of the UNGC, the Global Compact Local Network (GC LN), and government officials. The paper also assess es the role of hegemony enterprises and the embed ded hierarchy network in the UNGC governance. By insourcing the hegemony enterprises and outsourcing the "Regulatory Standard Setting" ( RSS) institute network within the regional political system, the UNGC can achieve the aim of global governance.
Keywords: 330; Enterprise Hegemony; Embedded Network; Enterprise Hierarchy; Global Compact; China